A justiça a partir do absurdo e da revolta em Albert Camus - Macário, Natália de Alexandre (2021)
The present work aims to clarify the concept and characteristics of justice from the absurdity and revolt, central axes of the existential analysis promoted by Albert Camus, in the essays Le Mythe de Sisyphe (1942) and L'Homme Révolté (1951). Although recurrent, the theme is diffuse and lacking specific delimitation. Studies on the subject attribute Camus' concern for justice to a more personal and political than philosophical inclination. The reconstitution of existential analysis, promoted in the essays, shows, however, the close relationship between justice and existential attributes. The fixation of a valid concept of justice can only emerge from the absurdity and revolt, central axes of thought of the Franco-Algerian author. Considered the purpose of the research, there is the reconstitution of the existential analysis, retaking the absurd as a starting point until culminating with the revolt. As a result, the absurdity reveals from the beginning that the emptying of justice is characteristic of the human condition. The revolt, on the other hand, will consist in the impulse toward the construction of justice, of which man is, by constitution, needy. In the end, it is possible to maintain that justice for Camus, as well as absurdity, corresponds to a passion, whose impossible satisfaction does not hinder the construction of human justice in revolt. The characteristics of Camusian justice differ according to the position assumed in the trials. As passion, injustice points to an ontological imperfection of man, unable to find full satisfaction with his desires. As human construction, it will be the result of the frustrated passion for justice, and therefore imperfect and limited, but the only possible human salvation